STRATEGIES FOR THE EFFECTIVE USE OF FIELD FORCE - Modise, Thabo Godfrey (My University, 2011)
This study explores the impact of field force monitoring tools on employee behaviour, with a focus on the use of Advantex by technicians in the North Rand area of Telkom SA. The purpose of the study was to investigate the impact that the use of Advantex has on employee relationships, with particular reference to communication, teamwork and motivation to work. The study will also looked at the impact that the tool has on performance, and their stress level. An evaluation of the attitude of the employees towards the tool was also conducted. The findings include that Advantex to the extent that it is used for the purpose of monitoring employees yields the same results as other surveillance and monitoring tools. There is an increase in the level of performance, but there is also an increase in the level of stress of the employees. The levels of teamwork are reduced as employees focus on achieving the targets that are set. Key focus areas that can assist in making the use of monitoring tools beneficial for all are identified.
MM - P&DM
Keywords: Field Force Monitoring Tools; Employee monitoring; Performance monitoring